2016
DOI: 10.1002/tcr.201600091
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Chiral Schiff Bases with C1 Symmetry in Metal‐Catalyzed Asymmetric Reactions

Abstract: In this Personal Account, various chiral Schiff base-metal-catalyzed enantioselective organic reactions are reported; the Schiff bases used were O,N,O- as well as N,N,P-tridentate ligands and N,N-bidentate ligands having C symmetry. In particular, the enantioselective addition of trimethylsilyl cyanide, dialkylzinc, and organozinc halides to aldehydes, enantioselective 1,4-addition of dialkylzinc to cyclic and acyclic enones, and asymmetric allylic oxidation are reported. Typically, ketimine-type Schiff base-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 241 publications
0
3
0
Order By: Relevance
“…The advantage of this reaction is that there is no requirement of strong acids or strong bases to activate the substrate molecule, which provides a better alternative to an aldol reaction where a strong base is employed to catalyze it. [60] However, many chiral catalysts were developed, catalyzing the enantioselective Reformatsky reaction with greater enantioselectivity and stereoselectivity. [61] Cozzi developed the first-ever catalytic enantioselective Reformatsky reaction of unsymmetrical ketones in the year 2006 by using an Mn-Salen catalyst.…”
Section: Enantioselective Reformatsky Reactionsmentioning
confidence: 99%
“…The advantage of this reaction is that there is no requirement of strong acids or strong bases to activate the substrate molecule, which provides a better alternative to an aldol reaction where a strong base is employed to catalyze it. [60] However, many chiral catalysts were developed, catalyzing the enantioselective Reformatsky reaction with greater enantioselectivity and stereoselectivity. [61] Cozzi developed the first-ever catalytic enantioselective Reformatsky reaction of unsymmetrical ketones in the year 2006 by using an Mn-Salen catalyst.…”
Section: Enantioselective Reformatsky Reactionsmentioning
confidence: 99%
“…In our measurements, citronellal was found to be unable to pass through HPLC columns and might cause damage to columns. Therefore, enantiomeric excess (ee) values were measured by CD and UV−vis spectra and calculated according to eq 4: 48 θ θ = × enantiomeric excess (ee) (%) 100 max (4) where θ is the CD value of the released solution and θ max is the CD value of the single enantiomer solution at the wavelength of 300 nm. The release solution and single enantiomer solution were kept at the same condition according to the UV absorption.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…The applications of Schiff bases have received ever-increasing attention because the characteristic chemical bond [−(CN)−] has excellent ion coordinative capability , and pH-responsive ability . Schiff bases and their derivatives have been widely used for developing catalyst intermediates, , biological sterilizations, , fluorescent reagents, , self-assembled polymers, , and polymer stabilizers . More recently, it was reported that Schiff bases can be used as electrodes for batteries and used to prepare metal–organic frameworks (MOFs) , and covalent organic frameworks (COFs) .…”
Section: Introductionmentioning
confidence: 99%